Essential Components of Quantitative Research: A Guide for Beginner Researchers - Faiqatul Munawwarah; Halimatus Sa’diyah; Iik Timamah; Faridatul Jannah (Penerbit Hellow Pustaka, 2025)
There are clear differences between quantitative and qualitative research. Therefore, it is important for novice researchers to understand the components of quantitative research. Many consider this research very difficult because it involves numbers in it. The purpose of this study is to explain the components of quantitative research to make it easier for novice researchers. The method in this study uses a conceptual approach with descriptive analysis. Problems in quantitative research are clear and not temporary. The classification of problems is a) descriptive problems, b) comparative problems c) associative problems. The variable that causes other variables is called the independent variable (X). The variable that is the result of causing other variables is called the independent variable (Y). The population is all subjects involved in the generalisation of the object. While the sample is part of the population. Taking it with sampling techniques. The theory of quantitative contains basic concepts relevant to problems and variables. The goal is to formulate hypotheses and instruments. Quantitative hypothesis is a temporary research conjecture. The form is Ha indicates the presence and H0 indicates the absence. Data from quantitative is statistical analysis.